2021
DOI: 10.3389/fpsyt.2021.685964
|View full text |Cite|
|
Sign up to set email alerts
|

Problematic Use of Alcohol and Online Gaming as Coping Strategies During the COVID-19 Pandemic: A Mini Review

Abstract: The COVID-19 (coronavirus disease 2019) pandemic has dramatically changed our daily lives and activities, including those originally intended to serve for leisure and pleasure. Drinking and online gaming became coping behaviors used to rescue ourselves from the stress and restricted lifestyle during the COVID-19 pandemic. However, frequent drinking and gaming can result in the pathological consequences of addiction. Those affected use the stimuli not to obtain pleasure, but rather to avoid the displeasure indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 66 publications
1
42
0
1
Order By: Relevance
“…Given that the onset of the COVID-19 pandemic occurred between the two data collection occasions, we feared this would interfere with some of the key variables in the present study (27)(28)(29). To control for this, we assessed mean differences and correlations between the two samples.…”
Section: Controlling For Effects Of Covid-19mentioning
confidence: 99%
“…Given that the onset of the COVID-19 pandemic occurred between the two data collection occasions, we feared this would interfere with some of the key variables in the present study (27)(28)(29). To control for this, we assessed mean differences and correlations between the two samples.…”
Section: Controlling For Effects Of Covid-19mentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19), first reported in November 2019, has created a global public health emergency. As of September 2021, the virus has infected over 267,000 people and caused over 2000 deaths in South Korea [1].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the restrictions related to COVID-19 challenge individual health behaviors that are typically embedded into structures related to work or school (Brazendale et al, 2017) as the context-dependent boundaries were longer available to many due to teleworking and home education. For example, several studies have identified a decline in physical activity and an increase in sedentary behavior (Stockwell et al, 2021), adverse changes in eating behavior (Bhutani et al, 2021;Herle et al, 2021;Robinson, Boyland, et al, 2021), as well as a substantial risk of problematic alcohol use and overuse of online gaming (Xu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%